BONUS DEMOGRAFI 2030: KESIAPAN GENERASI MUDA MEMAHAMI HAK DAN KEWAJIBAN SEBAGAI WARGA NEGARA INDONESIA - Anaya Syifa Wibowo; Faizal Dani Setiawan; Suparmi Suparmi (JURNAL ILMIAH NUSANTARA, 2026)
This study analyzes the level of understanding among Indonesian youth regarding their rights and obligations as citizens and its correlation with their preparedness to face the demographic dividend in 2030. The results of the literature review indicate that youth understanding remains suboptimal, influenced by conventional and non-interactive methods of Civics Education. Youth preparedness in leveraging the demographic dividend is affected by complex factors, including low human resource quality, high educated unemployment, stunting issues, and disparities in educational access and economic opportunities across regions. This research recommends comprehensive strategies to optimize the demographic dividend, encompassing the reform of contextual civics education, enhancement of digital literacy and civic engagement, strengthening the link-and-match between education and industry, fostering a youth entrepreneurship ecosystem, and promoting multisectoral collaboration in integrated policies. The success of these strategies is crucial for transforming the demographic dividend into an opportunity for national advancement towards a Golden Indonesia 2045, rather than allowing it to become a social and economic burden.